Absence of morphine-binding activity in serum from heroin addicts - Weksler, M. E. (1973)
Sera from heroin addicts and normal volunteers were assayed for their immuno-globulin concentration and for their capacity to bind (14)C-morphine. A significant increase in the serum concentration of immunoglobulin A, G and M was found in the serum of heroin addicts as compared to the normal subjects. Serum from only one addict was found to bind significant amounts of labelled morphine. As a group, sera from the addicts did not bind more (14)C-morphine than did normal serum.